The impact of working capital management on profitability of the listed companies in emerging European countries - Naumoski, Aleksandar (Review of Socio-Economic Perspectives RSEP, 2019)
This paper analyzes the impact that efficiency in working capital management has on the profitability of the companies. We have created a sample of 720 companies from ten South-East European countries (Bosnia and Herzegovina, Bulgaria, Montenegro, Croatia, Greece, North Macedonia, Romania, Slovenia, Serbia, and Turkey). Using their financial data in the period 2006–2015, we applied a panel regression model, involving operating profit ratio as a dependent variable, and several independent variables that represent the various features of the companies’ working capital, such as inventories turnover, days of collection of receivables, days of payment of accounts payable, and cash conversion cycle as a most comprehensive measure of the working capital management. In addition, we used a few control variables. The results of the model are expected to reveal which of these items, if any, have an impact on the profitability of the companies in the region. We found a statistically significant negative relationship of the profitability of the companies with the accounts receivable period and cash conversion cycle. Also, the relationship between the profitability and the inventory period is negative, but is not statistically significant. Profitability has a positive and statistically significant relationship with the accounts payable period. The companies of the SEE countries can increase operating profitability by shortening the period of collection of their receivables and the cash conversion cycle and by delaying their payments to creditors, taking care not to call into question good business relationships with them.
Keywords: corporate profitability, working capital management, cash conversion cycle, emerging countries, South-East European countries